Understanding teacher emotional exhaustion: exploring the role of teaching motivation, perceived autonomy, and teacher–student relationships - Wang, Xiaoyu; Yang, Li; Chen, Kun; Zheng, Yanan (Frontiers in Psychology, 2024)
Introduction This research investigates the complex interplay of factors influencing teacher emotional exhaustion within the educational environment. It draws upon a diverse sample of 680 teachers from 15 primary educational institutions in various districts of Shanghai, China. Methods The study examines the interrelationships among teacher-student relationships, perceived autonomy, teaching motivation, and emotional exhaustion. It employs validated scales to measure these constructs and utilizes Structural Equation Modeling (SEM) for analysis. Results The analyses using SEM reveal significant associations among the variables under study. The findings indicate robust correlations between positive teacher-student relationships, perceived autonomy, and higher teaching motivation. Concurrently, these factors exhibit a negative relationship with emotional exhaustion. Discussion Mediation analysis further unveils that teaching motivation plays a significant mediating role in the associations between teacher-student relationships, perceived autonomy, and emotional exhaustion. This emphasizes the intricate indirect effects of these constructs. Conclusion The study underscores the multifaceted nature of these factors and their collective impact on teacher well-being within educational settings. The implications derived highlight the importance for educational institutions to prioritize interventions fostering positive teacher-student relationships, autonomy-supportive environments, and intrinsic motivation among educators. These interventions aim to alleviate emotional exhaustion and enhance teacher well-being.